MicroRNA-372-3p Predicts Response of TACE Patients Treated with Doxorubicin and Enhances Chemosensitivity in Hepatocellular Carcinoma - Soliman, Marwa H.; Ragheb, Mohamed A.; Elzayat, Emad M.; Mohamed, Mervat S.; El-Ekiaby, Nada; Abdelaziz, Ahmed I.; Abdel-Wahab, Abdel-Hady A. (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Identification of factors to detect and improve chemotherapy-response in cancer is the main concern. microRNA-372-3p (miR-372-3p) has been demonstrated to play a crucial role in cellular proliferation, apoptosis and metastasis of various cancers including Hepatocellular Carcinoma (HCC). However, its contribution towards Doxorubicin (Dox) chemosensitivity in HCC has never been studied. Objective: This study aims to investigate the potential role of miR-372-3p in enhancing Dox effects on HCC cell line (HepG2). Additionally, the correlation between miR-372-3p and HCC patients who received Transarterial Chemoembolization (TACE) with Dox treatment has been analyzed. Methods: Different cell processes were elucidated by cell viability, colony formation, apoptosis and wound healing assays after miR-372-3p transfection in HepG2 cells Furthermore, the miR-372-3p level has been estimated in the blood of primary HCC patients treated with TACE/Dox by quantitative real-time PCR assay. Receiver Operating Curve (ROC) analysis for serum miR-372-3p was constructed for its prognostic significance. Finally, the protein level of Mcl-1, the anti-apoptotic player, has been evaluated using western blot. Results: We found a significantly higher level of miR-372-3p in the blood of the responder group of HCC patients who received TACE with Dox than of non-responders. Ectopic expression of miR-372-3p reduced cell proliferation, migration and significantly induced apoptosis in HepG2 cells which was coupled with a decrease of anti-apoptotic protein Mcl-1. Conclusion: Our study demonstrated that miR-372-3p acts as a tumor suppressor in HCC and can act as a predictor biomarker for drug response. Furthermore, the data referred for the first time its potential role in drug sensitivity that might be a therapeutic target for HCC.
Keywords: doxorubicin